Efficacy of favipiravir against influenza virus resistant to both baloxavir and neuraminidase inhibitors - Kiso, Maki; Yamayoshi, Seiya; Kawaoka, Yoshihiro (Journal of Antimicrobial Chemotherapy, 2023)
Abstract Objectives Widespread resistance of influenza viruses to neuraminidase (NA) inhibitor or polymerase inhibitor, baloxavir, is a major public health concern. The amino acid mutations R152K in NA and I38T in polymerase acidic (PA) are responsible for resistance to NA inhibitors and baloxavir, respectively. Methods We generated recombinant A(H1N1)pdm09 viruses possessing NA-R152K, PA-I38T or both mutations by using a plasmid-based reverse genetics system, characterized their virological properties in vitro and in vivo, and examined whether oseltamivir, baloxavir and favipiravir are effective against these mutant viruses. Results The three mutant viruses showed similar or superior growth kinetics and virulence to those of wild-type virus. Although oseltamivir and baloxavir blocked the replication of the wild-type virus in vitro, oseltamivir and baloxavir failed to suppress the replication of the NA-R152K and PA-I38T viruses in vitro, respectively. Mutant virus possessing both mutations grew in the presence of oseltamivir or baloxavir in vitro. Baloxavir treatment protected mice from lethal infection with wild-type or NA-R152K virus, but failed to protect mice from lethal infection with PA-I38T or PA-I38T/NA-R152K virus. Favipiravir treatment protected mice from lethal infection with all viruses tested, whereas oseltamivir treatment did not protect at all. Conclusions Our findings indicate that favipiravir should be used to treat patients with suspected baloxavir-resistant virus infection.